‘Therapy or no therapy, I’m still going to have unusual experiences [ … ] but it has [helped] the way that I feel and cope.’ A qualitative exploration of service user experiences of EMDRp and TF-CBTp in the ‘REducing psychosiS risk by TARgeting Trauma‘ study - Aidan Flinn; Filippo Varese; Marina Sandys; Amanda Larkin; Kim Cartwright; Clare Holden; Samantha Bowe; David Keane; Debbie Malkin; Diane Griffiths; Christopher D. J. Taylor; Sophie Parker; et al. (Frontiers in Psychiatry, 2026)
Introduction Traumatic experiences are common and exert substantial influence on clinical outcomes for individuals with an at-risk mental state for psychosis (ARMS). Despite a growing quantitative literature, no study has systematically examined ARMS service users’ qualitative perspectives on acceptability and feasibility of trauma-focussed interventions. The present study is the first to address this gap by exploring the views of ARMS participants who took part in the RESTART Trial, a feasibility trial comparing up to 24 sessions of EMDRp or TF-CBTp with Treatment as Usual. Methods A total of 22 ARMS participants completed semi-structured interviews. Data were analysed using the National Centre for Social Research Framework approach, guided by the Theoretical Framework of Acceptability. Purposeful sampling captured a wide range of demographic backgrounds and treatment experiences. Results Participants noted that both EMDRp and TF-CBTp were experienced as safe, effective, and acceptable. High perceived effectiveness, particularly for symptoms associated with post-traumatic stress, were reported. While reductions in ARMS experiences were noted, participants more often described a shift in their relationship to symptoms, gaining a greater sense of power and control. Participants demonstrated a clear understanding of the interventions and felt they aligned with their personal values. Although emotional burden and treatment demands were acknowledged, participants recommended some individually tailored adaptations to improve their impact. Discussion Our findings highlight the potential value of trauma-focussed interventions for ARMS, demonstrating that such therapies are viewed as acceptable, meaningful, and impactful. Larger-scale trials are needed to establish definitive clinical effectiveness, clarify mechanisms of change, and inform clinical guidelines.